An investigation of fatigue crack growth behavior of UIC 54 profile in high speed railway applications - Panerselvan, Gurubaran (School of Mechatronic Engineering, 2017)
The scope of the study is to investigate the fatigue strength and fatigue crack growth of railway rail steel grade 900A International Union of Railways (UIC 54) profile. The UIC 54 profile has been used to manufacture the rail by Malaysian railway for several decades. The 3D finite elements analysis is performed between wheel and rail to analysis maximum stress field distribution at rail inside curve region. Apart from that, the hardness measurements testing on UIC 54 profile at used and unused rail profile head. Furthermore, the hardness testing is conduct according to ASTM E 92-16 Standards. The dog-bone specimen and CT specimen experimental setup and testing are conducted according to ASTM E 466-15 and ASTM E 647-15 Standard, respectively. The fatigue strength (S-N) curve is plotted using seven dog-bone specimens with variable stress amplitude and with constant stress ratio of 0.1.